Trends of bivalve Bivalvia research in East Malaysia: a systematic review - Hamli, Hadi; Al Asif, Abdulla (Ebu Press, 2021)
The unique biodiversity in Malaysia makes this country a global hotspot for different aspects of research. Many European and non-native research activities are conducting by different research groups, whereas local institutions also collaborate with them to explore the pristine nature of west (peninsular Malaysia) and East Malaysia (Sarawak and Sabah province). East Malaysia is located in Borneo Island, and the biodiversity of this area are huge. The current review work scrutinized the information about the research activities on aquatic bivalve species and their different aspects of the investigation. This investigation revealed, to date 28 research publications were published on aquatic bivalves from eastern Malaysia, where biodiversity, conservation and ecology was the major aspect of research. The other aspects were aquaculture, natural history and taxonomy, nutritional study, reproduction of bivalve, morphology, and pollution can be mentionable. The major portion of this eastern Malaysia are not investigated and it is assumed that many species are still not reported. Further studies demand to explore the vast bivalve biodiversity of this part of Malaysia.